Autologous bone marrow-derived mesenchymal stem cells for interstitial fibrosis and tubular atrophy: a pilot study. Issue 1 (1st January 2021) - Zhang, Lei; Lai, Xingqiang; Guo, Yuhe; Ma, Junjie; Fang, Jiali; Li, Guanghui; Xu, Lu; Yin, Wei; Chen, Zheng
Abstract: Background: Mesenchymal stem cells (MSCs)-based therapy has shown promising results for renal injury. In this study, the efficacy and safety of autologous bone marrow-derived mesenchymal stem cells (BM-MSCs) in treating nonspecific interstitial fibrosis and tubular atrophy (IFTA) were evaluated. Methods: From March 2011 to January 2013, 11 renal transplanted patients with IFTA were recruited. At baseline, patients were given one intra-arterial infusion of BM-MSCs; 7 days and 1 month later, another two intravenous infusions of cells were followed. Serum creatinine, creatinine clearance rate, and serum cystatin-C at baseline and 7 days, 1 month, 3 months, 6 months, and 12 months after the intra-arterial infusion of BM-MSCs were used to assess renal function. At baseline and 6 months, histological examination based on hematoxylin-eosin, Masson's trichrome and periodic acid-Schiff staining and immunohistochemistry for transforming growth factor β1 (TGF-β1) and connective tissue growth factor (CTGF) was performed. Adverse events were recorded to evaluate the safety of BM-MSCs treatment. Results: At 12 months, the renal function of 6 patients (54.5%) was improved, 3 (27.3%) were stable and 2 (18.2%) were worsened. At 6 months, the mean IFTA scores of all participators were similar with the baseline (1.73 ± 0.41 vs.1.50 ± 0.0.77, p = 0.242); however, it was significantly decreased when only 6 patients with improved renal function were analyzed (1.67 ± 0.41 vs. 1.08 ± 0.20, p = 0.013). Besides, decreased expression of TGF-β1 and CTGF were also observed at 6 months. During 1 year follow-up period, only two minor complications including infection and allergy were observed. Conclusion: Our results demonstrated that autologous BM-MSCs are safe and beneficial for IFTA patients. Abbreviations : MSCs: mesenchymal stem cells; BM-MSCs: marrow-derived mesenchymal stem cells; IFTA: interstitial fibrosis and tubular atrophy; CAN: chronic allograft nephropathy; CNIs: calcineurin inhibitors; Scr: serum creatinine; CCr: creatinine clearance rate; Cys-C: cystatin-C; TGF-β1: transforming growth factor β1; CTGF: connective tissue growth factor